2006
DOI: 10.1073/pnas.0606701103
|View full text |Cite
|
Sign up to set email alerts
|

Similarities between heterophilic and homophilic cadherin adhesion

Abstract: The mechanism that drives the segregation of cells into tissuespecific subpopulations during development is largely attributed to differences in intercellular adhesion. This process requires the cadherin family of calcium-dependent glycoproteins. A widely held view is that protein-level discrimination between different cadherins on cell surfaces drives this sorting process. Despite this postulated molecular selectivity, adhesion selectivity has not been quantitatively verified at the protein level. In this wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
107
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(113 citation statements)
references
References 58 publications
(109 reference statements)
6
107
0
Order By: Relevance
“…The soluble, recombinant extracellular domain EC1-5 of Xenopus cleavage stage cadherin with a C-terminal hexahistidine tag was stably expressed in Chinese Hamster Ovary cells (27,28). The soluble, expressed hexahistidinetagged ectodomains were first purified by affinity chromatography on an Affi-Gel column (Bio-Rad, Hercules, CA), as described in Sivasankar et al (28).…”
Section: Methodsmentioning
confidence: 99%
“…The soluble, recombinant extracellular domain EC1-5 of Xenopus cleavage stage cadherin with a C-terminal hexahistidine tag was stably expressed in Chinese Hamster Ovary cells (27,28). The soluble, expressed hexahistidinetagged ectodomains were first purified by affinity chromatography on an Affi-Gel column (Bio-Rad, Hercules, CA), as described in Sivasankar et al (28).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies of actin reorganisation following cell-cell contact have employed cells grown on an artificial substrate, often using a 'calcium switch' to induce cadherin-mediated cell-cell contact (Ivanov et al, 2004;Zhang et al, 2005). Adhesion molecules such as cadherins (Goodwin and Yap, 2004;Leckband and Prakasam, 2006;Prakasam et al, 2006) and cell adhesion molecules (CAMs) (Crossin and Krushel, 2000;Walmod et al, 2004) (Gao et al, 2006;Modarresi et al, 2005) and coordinate cytoskeletal remodelling (Bamji, 2005;Goodwin and Yap, 2004;Yap and Kovacs, 2003). Both F-actin and E-cadherin are required for strong intercellular adhesion between mouse sarcoma cells brought together using a pair of micropipettes (Chu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, adhesion measurements and equilibrium binding studies showed that classical cadherins also form heterophilic bonds [4,9,12,14,15]. Generally, heterophilic affinities and bond energies are intermediate between the homophilic bonds of the two cadherin subtypes [4,9,10,12,14] (Table 2). …”
Section: Homophilic and Heterophilic Bindingmentioning
confidence: 99%
“…2F, solid line) gave the two-dimensional affinities and dissociation rates for EC1-EC1 bonds (Table 2) [9][10][11]. The relative affinities of homophilic N-and E-cadherin bonds differ from AUC measurements, but the 2D affinities correlated with the segregation of cells that express these proteins and with adhesion measurements [10,12]. The difference may arise from small sequence differences between the proteins studied, because single amino acid differences can alter the K A 's.…”
Section: Homophilic and Heterophilic Bindingmentioning
confidence: 99%